Pedagogical Knowledge on Peacebuilding Based on the Stories of Colombian Teachers in Rural Areas - Echavarría-Grajales, Carlos Valerio (2023)
Objective. To identify the pedagogical knowledge related to peacebuilding of rural teachers located in six departments of Colombia. Methodology. This article is derived from the second phase of the research study focused on the narratives written by 60 teachers from rural educational institutions in Colombia within the framework of territorial pedagogical missions. For the analysis, the information produced in the mixed communities of research, training, and innovation that constituted the participating teachers of this research was recorded, transcribed, and categorized into macrostructures of meaning. Results. The development of political, ethical, and citizenship skills contribute to realizing possible conditions that broaden human and institutional freedoms to make education and peace restored rights. Although the political, educational discourse and citizen experiences do not coincide, the pedagogical knowledge about peacebuilding results in a praxis that, when reflected upon, allows for validating conceptions and beliefs about coexistence, democracy, participation, human rights, respect for differences, dialogue, conflict resolution, and collaborative work. Conclusions. Building peace in rural schools makes a type of pedagogical knowledge explicit; it is related to the formative purposes of a culture of peace: historical memory, citizenship education, and human dignification.